Defect passivation with novel silicone copolymers for efficient perovskite light-emitting diodes. (2nd December 2020) - He, Fangru; Liu, Zhe; Qing, Jian; Zhao, Xinxin; Liu, Xinyan; Ma, Fulong; Dai, Yanpeng; Su, Shi-Jian; Hou, Lintao; Qi, Zhengjian
Abstract: Pinhole-free perovskite films with low defect density are essential to boost the efficiency of metal halide perovskite light-emitting diodes (PeLEDs). In this work, a novel amphiphilic silicone copolymer (Si14 -PEG14 -QAC) is introduced into perovskite as a passivation agent to improve the performance of PeLEDs. Si14 -PEG14 -QAC possesses polyethylene glycol and –NCH3 units, which can interact with perovskite by hydrogen bonding, resulting in high-quality perovskite films with small-size crystals, high coverage, low defect density, and enhanced photoluminescence quantum yield. Consequently, the perovskite films with Si14 -PEG14 -QAC enable efficient green PeLEDs with an external quantum efficiency of 4.5%, which is much higher than that of the control device without the polymer passivator (0.86%). This work suggests the great potential of silicone copolymers as passivation agents for high-quality perovskite films with high performance.